Antiplatelet aggregation triterpene saponins from the leaves of Ilex kudingcha. (September 2015) - Yang, Bao; Yang, Tao; Tan, Qinglong; Zhu, Jinping; Zhou, Lian; Xiong, Tianqin; Zhao, Zhongxiang; Jin, Jing
Graphical abstract: Highlights: Two new ursane-type and thirteen known triterpene saponins were identified from the leaves of Ilex kudingcha . All the compounds were screened for antiplatelet aggregation activity induced by ADP (5 μM) in vitro. Six compounds showed significant inhibition of platelet aggregation. Abstract: Two new ursane-type triterpene saponins, 3- O -β-d -glucopyranosyl(1 → 3)-[α-l -rhamnopyranosyl(1 → 2)]-α-l -arabinopyranosylurs-12, 19(29)-dien-28-oic acid 28- O -α-l -rhamnopyranosyl(1 → 2)-β-d -glucopyranosyl ester (1 ) and 3- O -β-d -glucopyranosyl(1 → 3)-[α-l -rhamnopyranosyl(1 → 2)]-α-l -arabinopyranosyl-19α, 20α-dihydroxyurs-12-en-28-oic acid 28- O -α-l -rhamnopyranosyl(1 → 2)-β-d -glucopyranosyl ester (2 ), along with thirteen known triterpene saponins were isolated from the n -BuOH part of the MeOH extraction of the leaves of Ilex kudingcha C.J. Tseng (also called "Ku-Ding-Cha"). The structures of new compounds were elucidated on the basis of detailed spectroscopic analysis, including HR-ESI-TOF-MS, 1D and 2D-NMR experiments, and by acid hydrolysis. All the compounds were screened for antiplatelet aggregation activity in vitro, and compounds1, 2, 3, 7, 12 and15 showed significant inhibition of platelet aggregation induced by ADP (5 μM) with IC50 values of 14.7 ± 3.7, 11.3 ± 2.5, 17.4 ± 4.6, 20.5 ± 3.1, 8.1 ± 1.5 and 18.9 ± 4.2 μM, respectively.